A 3D-polyphenylalanine network inside porous alumina: Synthesis and characterization of an inorganic–organic composite membrane - Jonathan Stott; Jörg J. Schneider (Beilstein Journal of Nanotechnology, 2020)
Surface functionalization of porous materials allows for the introduction of additional functionality coupled with high mechanical stability of functionalized inner pores. Herein, we investigate the surface-initiated ring-opening polymerization (SI-ROP) of phenylalanine-N-carboxyanhydride (PA-NCA) in porous alumina membranes (ALOX-membranes) with respect to different solvent mixtures (tetrahydrofuran (THF) and dichloromethane (DCM)). It was found that increasing the volume fraction of DCM leads to an increasing amount of fibrillar polymer structures within the porous ALOX-membrane. A three-dimensional fibrillar network with intrinsic porosity was formed in DCM, whereas in THF, a dense and smooth polypeptide film was observed. A post-treatment with a mixture of chloroform and dichloroacetic acid leads to rearrangement of the morphology of the grafted polymer films. The analysis by scanning electron microscopy (SEM), near-infrared spectroscopy (NIR) and contact angle measurements (CA) reveals a change in morphology of the grafted polymer films, which is due to the rearrangement of the secondary structure of the polypeptides. No significant loss of the surface-grafted polypeptides was determined by thermogravimetric (TG) measurements, which indicates that the change in morphology of the polymer films is solely a result of a conformational change of the surface-grafted polypeptides. Furthermore, adsorption of a test analyte (chloroanilic acid) was investigated with respect to different polymer functionalization schemes for reversed-phase solid phase extraction applications. The adsorption capability of the functionalized composite membrane was increased from 16.7% to 38.1% compared to the native ALOX-membrane.